The Checkpoint Regulator SLAMF3 Preferentially Prevents Expansion of Auto-Reactive B Cells Generated by Graft-vs.-Host Disease - Wang, Ninghai; Yigit, Burcu; van der Poel, Cees E.; Cuenca, Marta; Carroll, Michael C.; Herzog, Roland W.; Engel, Pablo; Terhorst, Cox (Frontiers in Immunology, 2019)
Absence of the mouse cell surface receptor SLAMF3 in SLAMF3-/- mice suggested that this receptor negatively regulates B cell homeostasis by modulating activation thresholds of B cell subsets. Here, we examine whether anti-SLAMF3 affects both B and T cell subsets during immune responses to haptenated ovalbumin [NP-OVA] and in the setting of chronic graft versus host disease (cGVHD) induced by transferring B6.C-H2bm12/ KhEg (bm12) CD4+ T cells into B6 WT mice. We find that administering αSLAMF3 to NP-OVA immunized B6 mice primarily impairs antibody responses and Germinal center B cell [GC B] numbers, whilst CXCR5+, PD-1+, and ICOS+ T follicular helper (TFH) cells are not significantly affected. By contrast, administering αSLAMF3 markedly enhanced autoantibody production upon induction of cGVHD by the transfer of bm12 CD4+ T cells into B6 recipients. Surprisingly, αSLAMF3 accelerated both the differentiation of GC B and donor-derived TFH cells initiated by cGVHD. The latter appeared to be induced by decreased numbers of donor-derived Treg and T follicular regulatory (TFR) cells. Collectively, these data show that SLAMF3-induced signaling is requisite to prevent autoantibody responses during cGVHD, but reduces responses to foreign antigens.